The potential for copper slag waste as a resource for a circular economy: A review – Part II - Phiri, Tina Chanda; Singh, Pritam; Nikoloski, Aleksandar N. (Minerals engineering, 2021)
Copper slag waste has continued to cause increasing concerns due to the huge volumes being produced annually worldwide. This paper presents a review of copper slag as a potential resource for cobalt and copper metals for a circular economy. An overview of the chemical and mineralogical characterisation of copper slag from 21 major producing countries is discussed. Characterisation is an important consideration in understanding the nature and environmental behaviour of copper slag. Copper smelter slags are highly heterogeneous and chemically diverse. The principal slag constituents are silica, ferrous oxide, ferric oxide, limestone, and alumina. The slag also contains high concentrations of valuable metals and metalloids such as copper, cobalt, zinc, calcium, aluminium, silver, magnesium, and lead. The variation in the chemical and mineralogical composition of copper slag is mainly influenced by the type of concentrate, type of fluxes, furnace type and cooling rates during and following the smelting and converting processes. Furthermore, the various processing strategies for metal recovery, such as flotation, pyrometallurgy and hydrometallurgy is presented. Finally, utilisation of the copper slag waste in the concrete industry to promote environmental sustainability is discussed. This review demonstrates that processing and repurposing of copper slag waste has benefits of a circular economy such as increasing critical metal supply, lowering the cost of concrete, and reducing environmental harm.